Regulatory effects of inhaled steroids on expression of matrix metalloproteinase-9 and its inhibitor in asthmatic rats - Qiao, Hong-mei (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2005)
OBJECTIVE: To investigate the role of matrix metalloproteinase-9 (MMP-9) and its tissue inhibitor (TIMP-1) in the pathogenesis of bronchial asthma and assess the effect of steroid treatment on MMP-9 and TIMP-1 levels. Matrix metalloproteinases are a family of zinc and calcium-dependent endopeptidases. Many MMPs such as MMP-1, MMP-2, MMP-3 are associated with asthma, in which MMP-9 is the key factor in asthma. Tissue inhibitor-1 of metalloproteinases is a specific inhibitor of MMP-9; the MMP-9 and TIMP-1 imbalance could lead to airway inflammation and remodeling in lung disease such as asthma